PENGARUH JENJANG PENDIDIKAN, LATAR BELAKANG PENDIDIKAN, LAMA BEKERJA DAN SOSIALISASI TERHADAP PERSEPSI IMPELEMNTASI SAK EMKM (Studi Empiris pada UMKM Kabupaten Kendal) - Endang Dwi W; Ageng Prasetyo (Neraca, 2018)
This study examine the effect of education level, educational background, length of work, and provision of information on the perception of the implementation of SAK EMKM at the Regency of Kendal in 2018, which was aimed for Accounting employees of SME. Data obtained from questionnaires, using incidental sampling method, obtained by respondents 45 people. Testing the hypothesis using multiple linear regression. The results of this study, education level and educational background partially did not affect the perception of SAK EMKM implementation, while the length of work and socialization partially affect and significantly the perception of SAK EMKM implementation. The levels of education, educational background, length of work and socialization variables simultaneously affect the perception of the implementation of SAK EMKM.